Etika Bisnis Islam: Pendekatan Siklus Ekonomi dan Praktik Bisnis Syariah dalam Ekspansi Waralaba Industri Retail - Eva Rosyidah; Khusniati Rofiah (Syntax Corporation Indonesia, 2024)
In this era of globalization, franchise expansion has become one of the main strategies for the growth of the retail industry. However, in a business context governed by Islamic principles, the concept of business ethics becomes increasingly relevant. This article explores the role of Islamic Business Ethics in the context of franchise expansion in the retail industry, with a focus on economic cycles and sharia business practices. Through a literature review, this article describes how Islamic business ethical values can direct franchise expansion steps, manage risks in fluctuating economic cycles, and implement sharia business practices that are in accordance with Islamic principles. This research discusses the implications of Islamic business ethics in strengthening the foundations of sustainability and long-term success for the retail industry which focuses on the principles of justice, social responsibility and economic balance. The research results show that the application of Islamic business ethics in franchise expansion in the retail industry can improve business performance, strengthen consumer trust, and promote business sustainability. This research highlights the importance of understanding and applying the principles of Islamic business ethics in the context of modern business, especially in the retail industry.